CyberPatriot - Linthicum, Steven W.; Boose, Cherokee (Packt Publishing, 2024)
The course unfolds with a comprehensive introduction to cybersecurity, spanning essential topics like online safety, ethics, and current events. Delving deeper, participants explore core principles, including the CIA Triad, threats, and vulnerabilities. From fundamental to advanced levels, the course covers cybersecurity techniques with hands-on experience in both Microsoft Windows and Linux environments. Navigating through networking basics, Microsoft Windows history, and security tools, the course emphasizes account management, security policies, and tools. A thorough examination of Ubuntu and Linux security, encompassing both graphical and command-line interfaces, ensures a well-rounded understanding. The course continues by unraveling the intricacies of computer operations, virtualization, and performance monitoring. Introducing Linux and Ubuntu, the course covers command-line usage, security measures, and advanced techniques. In the final stretch, you will explore ethical hacking tools and techniques, developing critical security analysis and incident response skills. The course concludes with advanced Ubuntu security, providing a comprehensive skill set for tackling evolving cyber threats. What you will learn Grasp the CIA Triad principles Implement basic and advanced cybersecurity techniques Navigate Microsoft Windows and MSDN Understand Linux and Ubuntu fundamentals Apply ethical hacking tools and techniques Develop critical incident response skills Audience This course is ideal for students and professionals seeking to excel in cybersecurity. A basic understanding of computer basics is recommended. Perfect for those aspiring to enhance their skills and adapt to the evolving landscape of cybersecurity. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Steve Linthicum: Steven W. Linthicum was a professor of computer science at Sierra College in Rocklin, California, retiring from his role in June 2017. Steve continues to teach and support other community college faculty in a variety of classes that focus on network administration, information assurance and security, and virtualization/cloud technologies. Steve has always been on the leading edge of technology, holding a variety of industry certifications issued by major industry leaders like Microsoft, VMware, CompTIA, ISC2, EMC, and Citrix. Cherokee Boose: Cherokee Boose started as a computer technician and moved to a network administrator role. Her love for learning is what pushed her towards a career in IT education. Certifications: MCSE Cloud Platform and Infrastructure; MCSA: Server 2012; MCT; MCP; MTA: Networking Fundamentals; MTA: Windows Operating System Fundamentals; Six Sigma Green Belt; CompTIA A+, A+ CE, Network+, CTT+, and Cloud+.
Online resource; title from title details screen (O'Reilly, viewed February 27, 2024)
Keywords: Penetration testing (Computer security); Computer security; Tests d'intrusion; Sécurité informatique; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet